DNA hypermethylation profiles associated with glioma subtypes and EZH2 and IGFBP2 mRNA expression - Zheng, Shichun (Oxford University Press, 2011)
We explored the associations of aberrant DNA methylation patterns in 12 candidate genes with adult glioma subtype, patient survival, and gene expression of enhancer of zeste human homolog 2 (EZH2) and insulin-like growth factor-binding protein 2 (IGFBP2). We analyzed 154 primary glioma tumors (37 astrocytoma II and III, 52 primary glioblastoma multiforme (GBM), 11 secondary GBM, 54 oligodendroglioma/oligoastrocytoma II and III) and 13 nonmalignant brain tissues for aberrant methylation with quantitative methylation-specific PCR (qMS-PCR) and for EZH2 and IGFBP2 expression with quantitative reverse transcription PCR (qRT-PCR). Global methylation was assessed by measuring long interspersed nuclear element-1 (LINE1) methylation. Unsupervised clustering analyses yielded 3 methylation patterns (classes). Class 1 (MGMT, PTEN, RASSF1A, TMS1, ZNF342, EMP3, SOCS1, RFX1) was highly methylated in 82% (75/91) of lower-grade astrocytic and oligodendroglial tumors, 73% (8/11) of secondary GBMs, and 12% (6/52) of primary GBMs. The primary GBMs in this class were early onset (median age 37 years). Class 2 (HOXA9 and SLIT2) was highly methylated in 37% (19/52) of primary GBMs. None of the 10 genes for class 3 that were differentially methylated in classes 1 and 2 were hypermethylated in 92% (12/13) of nonmalignant brain tissues and 52% (27/52) of primary GBMs. Class 1 tumors had elevated EZH2 expression but not elevated IGFBP2; class 2 tumors had both high IGFBP2 and high EZH2 expressions. The gene-specific hypermethylation class correlated with higher levels of global LINE1 methylation and longer patient survival times. These findings indicate a generalized hypermethylation phenotype in glioma linked to improved survival and low IGFBP2. DNA methylation markers are useful in characterizing distinct glioma subtypes and may hold promise for clinical applications.